2017
DOI: 10.5152/npa.2017.18062
|View full text |Cite
|
Sign up to set email alerts
|

Increased Hyperacusis with Risperidone in an Autistic Child

Abstract: Hyperacusis has been defined as "unusual tolerance to ordinary environmental sounds" or "consistently exaggerated or inappropriate responses to sounds" that are neither uncomfortably loud nor threatening to a typical person. In most cases, the underlying medical condition cannot be found, but it can be related with some diseases, syndromes, and developmental and mental disorders (1). Autistic spectrum disorder (ASD) is one of these disorders found to be related with hyperacusis, which is a neurodevelopmental d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In addition to possible anatomical and physiological causes of hyperacusis, outside factors possibly contributing to hyperacusis in the autism population have been found in the literature, including a recent case study of an autistic 11 year-old boy, whose hyperacusis worsened when he was taking risperidone to treat hyperactivity and behavioral problems [ 47 ]. However, a contrasting case study noted an autistic five and a half year-old girl whose hyperacusis, according to parent report, alleviated after taking the same medication [ 48 ].…”
Section: Hyperacusis and Asdmentioning
confidence: 99%
“…In addition to possible anatomical and physiological causes of hyperacusis, outside factors possibly contributing to hyperacusis in the autism population have been found in the literature, including a recent case study of an autistic 11 year-old boy, whose hyperacusis worsened when he was taking risperidone to treat hyperactivity and behavioral problems [ 47 ]. However, a contrasting case study noted an autistic five and a half year-old girl whose hyperacusis, according to parent report, alleviated after taking the same medication [ 48 ].…”
Section: Hyperacusis and Asdmentioning
confidence: 99%
“…However, while everyday sounds can be extremely painful and loud in hyperacusis; in patients with misophonia, it is a specific sound that produces an aversive reaction [ 16 ]. While case reports support using risperidone as a potential treatment option for hyperacusis in patients with autism, we are unaware of published reports on using risperidone to treat misophonia in this patient population [ 17 , 18 ]. Here, we discuss the case of a 32-year-old male with ASD whose misophonia responded dramatically to risperidone.…”
Section: Introductionmentioning
confidence: 99%
“…3 Many studies have reported that children with hyperacusis, especially those attending school, feel uncomfortable or anxious due to stimuli, such as classroom noise, physical education class sounds, and fire alarms. 4,5 This may cause children to avoid situations or environments in which they perceive loud noises. 6 In one study, a child with hyperacusis disrupted the other students' concentration during exams due to noise disturbance.…”
mentioning
confidence: 99%